BIBLICAL LEADERSHIP CHARACTER OF GOD - Lumingkewas, Edwin Melky (Klabat Theological Review, 2022)
Spiritual leadership has become a growing interest among Christians. Among leadership in the Seventh-day Adventist Church, It is important to have a basic perspective of Christian leadership based on leadership principles from God as found in the Bible. The Bible indicates that God is leader. Although Bible is absent of trinity word, the description of the triune God is clear. In this trinity relationship, the nature of divine leadership is implied. As God the Father sent Jesus Christ, then Jesus sent the Holy Spirit in the salvation context, the concept of leadership is there. God leading the nation of Israel also provides additional information about the nature of God's leadership. Then, God's act of organizing, executing, and evaluating the creation of this world's represents a part of the biblical leadership process. Furthermore, spiritual leadership traits such as: Loving, humble, and care are shown by God. Keywords: Leadership, Character Bibliography Andrews, E. D. (2016). Understanding the creation account: Basic Bible doctrines of the Christian faith. Cambridge, OH: Christian. Bergant, D., & Karris, R. J. (1989). The Collegeville Bible commentary: Based on the New American Bible with revised New Testament. Collegeville, MN: Liturgical. Cooper, L. C. (2015). Code of conduct for a Seventh-day Adventist leader. In P. H. Douglas (Ed.), Transparency and accountability: A global commitment of Seventh-day Adventist Church leaders (pp. 33-68). San Antonio, TX: General Conference Auditing Service. Crisp, O. D. (2007). Divinity and humanity: The Incarnation reconsidered. Cambridge, UK: Cambridge University Press. Davidson, R. M. (2014). Leadership language in the Old Testament. In S. Bell (Ed.), Servants and friends: A biblical theology of leadership (pp. 11-30). Berrien Springs, MI: Andrews University Press. Doukhan, J. B. (2014). The creative narration. In S. Bell (Ed.), Servants and friends: A biblical theology of leadership (pp. 31-48). Berrien Springs, MI: Andrews University Press. Graves, O. E. (2012). God created man in His image and likeness. Bloomington, IN: Trafford. Grudem, W. (1994). Systematic theology: An introduction to biblical doctrine. Grand Rapids, MI: Zondervan. Hebblethwaite, B. (1987). The Incarnation: Collected essays in Christology. Cambridge, UK: Cambridge University Press. Jemison, T. H. (1959). Christian beliefs: Fundamental biblical teachings for Seventh-day Adventist college classes. Boise, ID: Pacific Press. Louth, A., Conti, M., & Oden, T. C. (Eds.). (2001). Genesis 1-11. Downers Grove, IL: InterVarsity. Mendoza, J. A. (2010). Heaven on earth: A guide to the kingdom. Bloomington, IN: AuthorHouse. Merrit, J. (2011). God, I’ve got a question: Biblical truth for our deepest concerns. Eugene, OR: Harvest. Metzger, P. L. (2011). Why should we care? Cultural Encounters, 7(1), 7-20. Retrieved November 3, 2015, from goo.gl/7ydETL Nichol, F. D. (Ed.). (1957-1978). Seventh-day Adventist Bible commentary (Vols. 1 & 7). Washington, DC: Review & Herald. Paago, S. (2012). God’s law. Bloomington, IN: WestBow. Piper, J. (1996). Four ways God leads His people. Retrieved from http://www.desiring.org/articles/four-ways-god-leads-his-people Radmacher, E. D., Allen, R. B., & House, H. W. (1999). Nelson’s new illustrated Bible commentary: Gen 1:26. Nashville, TN: Thomas Nelson. Rae, M. A. (1997). Kierkegaard’s vision of the Incarnation. New York, NY: Oxford University Press. Rinehart, S. T. (1998). Upside down: The paradox of servant leadership. Quezon City, Philippines: Navigator. Schlessinger, L., & Vogel, R. S. (1998). The Ten Commandments: The significance of God’s laws in everyday life. New York, NY: Cliff Street. Shore, M. H. (2014). “Jesus, remember me”: Biblical imagination and the experience of dementia. Word & World, 34(3), 264-272. Retrieved from https://wordandworld.luthersem.edu/content/pdfs/34-3_Igniting_Bib_Imagination/34-3_Shore.pdf Stump, E. (2009). Atonement according to Aquinas. In M. Rea (Series Ed.), Oxford Reading Philosophical Theology: Vol. 1. Trinity, Incarnation, atonement (pp. 267-293). New York, NY: Oxford University Press. Suh, C. W. (1982). The creation-mediatorship of Jesus Christ: A study in the relation of the incarnation and the creation. Amsterdam, Netherlands: Rodopi. Unger, M. F. (1981). Unger’s commentary on the Old Testament. Chicago, IL: Moody Press. Walvoord, J. F., & Zuck, R. B. (Eds.). (1983). The Bible knowledge commentary: An exposition of the Scriptures. Wheaton, IL: Victor. White, E. G. (1911). The acts of the apostles. Mountain View, CA: Ellen G. White Estate. White, E. G. (1958). The story of patriarchs and prophets: As illustrated in the lives of holy men of old. Mountain View, CA: Pacific Press. White, E. G. (1985). Christian leadership. Washington, DC: Ellen G. White Estate.